The Silk Route: A Dynamic Cross Border Trading - Islam, Arshad (2021)
The SilkRoute was not a single road, but a sprawling trading network linking China with West Asia. It was the essential conveyance route linking ancient China with Western Europe for over14,000 miles. On foot, a single trip would take more than a year. It served as a conduit between Asia and Europe and a lifeline for the economic growth and political and military activities of the communities it nourished. The chief artery of the Silk Route was Central Asia, spanning all of the major urban centres of the region – Nishapur, Tabriz, Ghazna, Merv, Sarakhs, Termez, Bukhara, Samarkand, Chach, Urgench, Isfijab, Taraz, Utrar, Balasaghun, Kayalik, Almalïk, Akhsikath and Kashghar. Each of them was a confluence of several minor roads that linked the main highway with provinces and regions, mountain valleys and the Steppes.